System modelling and simulation - IMACS Symposium on System Modelling and Simulation (1988 : Cetraco, Italy); Tzafestas, Spyros G.; Eisenberg, Alfredo; Carotenuto, Luciano (Amsterdam : North-Holland, 1989)
57